2015
DOI: 10.1186/s13613-015-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Withholding or withdrawal of treatment under French rules: a study performed in 43 intensive care units

Abstract: BackgroundIn France, decisions to limit treatment fall under the Leonetti law adopted in 2005. Leading figures from the French world of politics, science, and justice recently claimed for amendments to the law, considering it incomplete. This study, conducted before any legislative change, aimed to investigate the procedural aspects of withholding/withdrawing treatment in French ICUs and their adequacy with the existing law.MethodsThe characteristics of patients qualified for a withholding/withdrawal procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
52
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 48 publications
13
52
2
3
Order By: Relevance
“…Data from the North American SUP-PORT and European Ethicus studies also documented that information about a patient's wishes regarding EOL decisions was available in only 20% of competent patients [38,39]. This was, again, confirmed in more recent studies [40,41], in which only 57% of families were involved in providing information related to EOL decisions in VOPs. A recent Asian study of elderly (mean greater than 80 years old) patients in ICU similarly reported that pre-acute event advance directives were documented in less than 3% of reviewed cases in ICU [42].…”
Section: Patients' Wishes and Directivesmentioning
confidence: 82%
“…Data from the North American SUP-PORT and European Ethicus studies also documented that information about a patient's wishes regarding EOL decisions was available in only 20% of competent patients [38,39]. This was, again, confirmed in more recent studies [40,41], in which only 57% of families were involved in providing information related to EOL decisions in VOPs. A recent Asian study of elderly (mean greater than 80 years old) patients in ICU similarly reported that pre-acute event advance directives were documented in less than 3% of reviewed cases in ICU [42].…”
Section: Patients' Wishes and Directivesmentioning
confidence: 82%
“…Contrary to ethicists (22,45,46), many intensivists clearly distinguish between "withholding" and "withdrawal" decisions, with the former being perceived as more passive (47)(48)(49)(50)(51)(52). By establishing a three-level hierarchy of decisions ("stop" > "do not increase" > "do not start"), a French epidemiological survey demonstrated that the more "active" limitations (withdrawal of life-sustaining therapy) mostly involved severely braininjured patients (post-anoxic coma, stroke, head trauma), whereas patients with chronic respiratory disease, preexisting disability affecting autonomy or cognition, and/or respiratory failure on admission had treatment preferentially withheld rather than withdrawn (53). This study was conducted before the Maastricht III program was launched in France, under conditions enabling a state-of-play of practices without the physicians responsible for WhWd decisions being pressured by any © Annals of Translational Medicine.…”
Section: Caregivers Have Equal Responsibility Towards Both the Dying mentioning
confidence: 99%
“…Brain-injured patients are rarely or never conscious at the time of the decision-making and cannot be involved in the discussions. In the survey mentioned above, the low level of patients being directly or indirectly involved in the decision-making (23%) may reflect that many were unable to express their preferences once hospitalized, and/or that they did not anticipate such conditions of being before admission (53). While the French law authorizing such practices was passed in 2005, the prevalence of advance directives and designated surrogate persons remains low (53).…”
Section: Caregivers Have Equal Responsibility Towards Both the Dying mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widespread belief that shared decision-making is firmly embedded in clinical practice, a recent French study reported that only 13% of elderly competent ICU patients had been asked about their treatment preferences [30]. Studies from both North America and Europe also documented that information about a patient's wishes regarding EOL decisions was available in only 20% of competent patients [31,32].…”
Section: Frailty Measurement As Applied To Clinical Practicementioning
confidence: 99%